2022
DOI: 10.3389/fped.2022.886450
|View full text |Cite
|
Sign up to set email alerts
|

Sonographic Evaluation of the Endotracheal Tube Position in the Neonatal Population: A Comprehensive Review and Meta-Analysis

Abstract: BackgroundEndotracheal intubation in neonates is challenging and requires a high level of precision, due to narrow and short airways, especially in preterm newborns. The current gold standard for endotracheal tube (ETT) verification is chest X-ray (CXR); however, this method presents some limitations, such as ionizing radiation exposure and delayed in obtaining the radiographic images, that point of care ultrasound (POCUS) could overcome.Primary ObjectiveTo evaluate ultrasound efficacy in determining ETT place… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
18
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(18 citation statements)
references
References 46 publications
0
18
0
Order By: Relevance
“…In a recent large meta‐analysis including 14 studies and 602 newborn patients, ultrasound identified the presence of ETT in 96.8% of the evaluations. The mean time to confirmation of ETT was also substantially lower with ultrasound 23 …”
Section: Endotracheal Tube Placement and Depth Confirmationmentioning
confidence: 86%
See 2 more Smart Citations
“…In a recent large meta‐analysis including 14 studies and 602 newborn patients, ultrasound identified the presence of ETT in 96.8% of the evaluations. The mean time to confirmation of ETT was also substantially lower with ultrasound 23 …”
Section: Endotracheal Tube Placement and Depth Confirmationmentioning
confidence: 86%
“…It has been studied in neonates and children in neonatal intensive care units, pediatric intensive care units, emergency departments, and by a transport team. It compares favorably with chest x‐ray and capnography in its ability to locate the tube endotracheally and to ensure that it is not in a mainstem bronchus, and may augment other ETT verification methods 21–25 …”
Section: Endotracheal Tube Placement and Depth Confirmationmentioning
confidence: 99%
See 1 more Smart Citation
“…between esophageal and tracheal intubation 1,2 . The need to position an unstable newborn during X-ray imaging may also result in tube dislodgement and even extubation.…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…The total time taken by ultrasound to confirm ETT tip location and assessing the distance between the tip and arch of the aorta could have given additional information regarding how faster the procedure can be done in emergency or intensive care setting since the time taken by the procedure might vary from seconds to minutes which is much quicker than chest X-ray. 3 …”
mentioning
confidence: 99%